2010
DOI: 10.4269/ajtmh.2010.09-0713
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Association of Common Red Blood Cell Polymorphisms with Plasmodium falciparum Infection and Uncomplicated Malaria in Papua New Guinean School Children

Abstract: * Gene locus, allele names, genotype designations, and phenotypes as described in Table 1 . † LDR-FMA = post-PCR ligase detection reaction-fluorescent microsphere assay for diagnosis of 4 Plasmodium parasites of humans. ‡ LM = light microscopy, or conventional blood smear, light microscopy diagnosis of four Plasmodium parasites of humans. § Clinical Episode = febrile episode with concurrent P. falciparum parasitaemia > 5,000/μL. ¶ MTR = median time to re-infection (days), IR = incidence rate (/child/yr) for en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…56,6264 In one prospective study of children in Papua New Guinea, both α-thalassaemia homozygotes (IRR 0.51; 95% CI 0.32 – 0.81) and heterozygotes (IRR 0.56; 95% CI 0.36 – 0.87) had fewer episodes of PCR-detectable parasitaemia than those without α-thalassaemia, 67 though this outcome has not been investigated in other studies.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…56,6264 In one prospective study of children in Papua New Guinea, both α-thalassaemia homozygotes (IRR 0.51; 95% CI 0.32 – 0.81) and heterozygotes (IRR 0.56; 95% CI 0.36 – 0.87) had fewer episodes of PCR-detectable parasitaemia than those without α-thalassaemia, 67 though this outcome has not been investigated in other studies.…”
Section: Resultsmentioning
confidence: 98%
“…Second, the dissimilarity of estimates from prospective studies of the risk of uncomplicated falciparum malaria in homozygous α-thalassaemic children is striking, with significantly increased risk on the southwestern Pacific island of Vanuatu 39 but either slightly decreased or unchanged risk in Africa and Papua New Guinea (Table 2). 31,35,40,67,96 Other data have suggested an increased Plasmodium prevalence in homozygous α-thalassaemics in Papua New Guinea, 97 underscoring that haemoglobinopathies may have variable effects in different settings upon different outcomes. Future studies are needed to more definitively characterize these effects and define their relationship with host genetics, malaria epidemiology, and acquired immunity to malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas many more studies have recorded, the clinical relationship between a thalassemia and malaria, the results have not been entirely consistent. The incidence of uncomplicated clinical malaria has been lower in a thalassemic than normal subjects in some cohort studies (Wambua et al 2006;Enevold et al 2008), whereas in others the incidence has either been equal (Lin et al 2010;Veenemans et al 2011) or even higher (Williams et al 1996;Veenemans et al 2011). Conversely, studies focused on severe malaria have shown consistent evidence for a strongly protective effect that is generally more marked in homozygous than heterozygous subjects (Allen et al 1997;Mockenhaupt et al 2004b;Williams et al 2005d;Wambua et al 2006;May et al 2007).…”
Section: The Thalassemiasmentioning
confidence: 97%
“…In disagreement with this finding, in Thailand two reports showed that low CR1 densities (homozygotes for LL) are not associated with protection from severe disease forms (Nagayasu et al, 2001;Teeranaipong et al, 2008). Several other studies further contribute to this discrepancy between reports (Fowkes et al, 2008;Kosoy et al, 2011;Lin et al, 2010;Panda et al, 2012;Rout et al, 2011;Sinha et al, 2009). Overall, no general rules can be proposed whether or not CR1 density on erythrocytes protects from malaria pathologies.…”
Section: Cr1 Expression Polymorphismmentioning
confidence: 49%